THERMOELECTRIC SEMICONDUCTOR ENERGY CONVERTER TO RECTIFY THE AC VOLTAGE - T. A. Ismailov; A. G. Mustafaev; D. K. Ramazanova; A. B. Sulin (Вестник Дагестанского государственного технического университета: Технические науки)
The paper discusses existing means for rectifying alternating electrical signal with inherent advantages and disadvantages. The proposed design of the AC voltage, made on the basis of the thermoelectric Converter using renewable solar energy. Made a rough calculation of this device.